Silicone Joint Dimensioning Calculation Methods - Pierre Descamps (Challenging Glass Conference, 2018)
Historically, silicone joint dimensioning is calculated with a simplified equation implemented in various standards for structural glazing. This equation assumes homogeneous stress distribution along the sealant bite whilst high local stress peaks, structure deformation or material ageing are included in a global safety factor. Safeguards such as a maximum authorized deflection (1%) and aspect ratio to respect (between 1 and 3) have been given to ensure the validity of the used equations. However new trends in commercial buildings such as the use of large dimensions glass panes or stronger engineering performance requirements such as high windloads above 5000Pa lead to the non-respect of these guidelines and the impossibility to use the simplified equation. An improved mathematical relationship making a direct correspondence between a joint included in a façade system and the behavior of a test piece was recently proposed by the authors. The goal of this article is to further validate the proposed relationship by confronting predictions with physical measurements on various test samples and the results from FEA modeling. The domain of validity of the simplified equation and the improved equation will be developed.